Gambaran Student Engagement pada Siswa SMA (Studi Kasus pada Siswa MAN 1 Magelang) - Junianto, Mahmud; Bashori, Khoiruddin; Hidayah, Nurul (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
High student engagement will make students to avoid adolescent delinquency, reduce dropout rates, and play a positive role in student learning achievement, while low student engagement will result in students being less diligent in learning in the classroom, less diligent in doing homework, and have less effort to improve academic performance. So important is student attachment that it needs to be given special attention. The purpose of this study is to obtain preliminary data on the description of student attachment which will then be used to improve student attachment in upper secondary schools. The subjects of the study were MAN 1 Magelang students totaling 100 students selected using random cluster sampling technique. The findings show that there are 51 students with high attachment level and 49 students with low attachment. In addition, there is a difference in the level of student engagement in the sex of men and women, where women have a higher level of engagement than male students who have a high attachment due to the support of teachers, friends, and assignment characteristics. While students who have an attachment that is because parents do not pay attention to the good development of the child, the teacher is considered favoritism, friendships and engage in behavior that lead to negative side.